From Skin to Kidneys: The Cutaneous Clues of Renal Disease in Children - Mario Diplomatico; Pierluigi Marzuillo; Angela La Manna; Andrea Apicella; Stefano Guarino; Vincenzo Piccolo (Mattioli1885, 2020)
Background:  The skin is often seen as a world apart, but not rarely do cutaneous manifestations reveal signs of systemic disease. Objectives: The aim of this review is to include in one paper all the possible correlations between nephrological and dermatological manifestations of the same disease in pediatric patients while also keeping in mind that in apparent exclusively dermatological  diseases there can be nephrological manifestations as part of the same disorder and vice versa. Methods: We searched on PubMed for a possible link between skin and kidney matching the following terms and correlated MeSH terms: dermatology, skin, kidney, renal disease, nephrology, pediatrics, child, childhood, vasculitis, and cancer. We selected only articles reporting a link between nephrology and dermatology in pediatrics, and they are all included in this comprehensive review. Results: Kawasaki disease, Henoch-Schönlein purpura, systemic lupus erythematosus, Dent disease, subcutaneous fat necrosis, Langerhans cell histiocytosis, renal cell carcinoma, non-Hodgkin lymphoma, tuberous sclerosis complex and syndromes with increased risk for Wilms tumor, Fabry disease, nail-patella syndrome, neurofibromatosis type 1, Beckwith-Wiedemann syndrome, Adams-Oliver syndrome 1, Apert syndrome, Fanconi pancytopenia syndrome, Pallister-Hall syndrome, and Fanconi pancytopenia syndrome are all conditions in which there can be both nephrological and dermatological manifestations in children. Conclusions: We could not any find reports that focused attention on the link between nephrological and dermatological manifestations of the same disease in children. It is also important for clinicians to keep in mind that in what may appear to be an exclusively dermatological disease, there can be nephrological manifestations as part of the same disorder and vice versa.